Александр Сергеевич Пушкин - Филин Михаил Дмитриевич (Русскiй мiръ в лицах, 2006)
Экземпляры: ф.6 (20190722) / Инвентарный номер: 2743 И / Цена: / Сис.шифр: 83.3(2Рос=Рус)1 / Авт.знак: А 46 / ГРНТИ: 17.09 / ББК: 83.3(2Рос=Рус)1-8 Пушкин